The vertical propagation of disturbances triggered by seismic waves of the 11 March 2011 M9.0 Tohoku earthquake over Taiwan. Issue 4 (24th February 2016) - Liu, J. Y.; Chen, C. H.; Sun, Y. Y.; Chen, C. H.; Tsai, H. F.; Yen, H. Y.; Chum, J.; Lastovicka, J.; Yang, Q. S.; Chen, W. S.; Wen, S.
Abstract: In this paper, concurrent/colocated measurements of seismometers, infrasonic systems, magnetometers, HF‐CW (high frequency‐continuous wave) Doppler sounding systems, and GPS receivers are employed to detect disturbances triggered by seismic waves of the 11 March 2011  M 9.0 Tohoku earthquake. No time delay between colocated infrasonic (i.e., super long acoustic) waves and seismic waves indicates that the triggered acoustic and/or gravity waves in the atmosphere (or seismo‐traveling atmospheric disturbances, STADs) near the Earth's surface can be immediately activated by vertical ground motions. The circle method is used to find the origin and compute the observed horizontal traveling speed of the triggered infrasonic waves. The speed of about 3.3 km/s computed from the arrival time versus the epicentral distance suggests that the infrasonic waves (i.e., STADs) are mainly induced by the Rayleigh waves. The agreements in the travel time at various heights between the observation and theoretical calculation suggest that the STADs triggered by the vertical motion of ground surface caused by the Tohoku earthquake traveled vertically from the ground to the ionosphere with speed of the sound in the atmosphere over Taiwan. Key Points: Rayleigh waves instantly induce the colocated infrasonic waves Traveling seismo‐atmosphere disturbances travel with the sound speed Apply the circle method on seismo‐generated infrasonic waves